Cytokines: From Clinical Significance to Quantification. Issue 15 (10th June 2021) - Liu, Chao; Chu, Dewei; Kalantar‐Zadeh, Kourosh; George, Jacob; Young, Howard A.; Liu, Guozhen
Abstract: Cytokines are critical mediators that oversee and regulate immune and inflammatory responses via complex networks and serve as biomarkers for many diseases. Quantification of cytokines has significant value in both clinical medicine and biology as the levels provide insights into physiological and pathological processes and can be used to aid diagnosis and treatment. Cytokines and their clinical significance are introduced from the perspective of their pro‐ and anti‐inflammatory effects. Factors affecting cytokines quantification in biological fluids, native levels in different body fluids, sample processing and storage conditions, sensitivity to freeze‐thaw, and soluble cytokine receptors are discussed. In addition, recent advances in in vitro and in vivo assays, biosensors based on different signal outputs and intracellular to extracellular protein expression are summarized. Various quantification platforms for high‐sensitivity and reliable measurement of cytokines in different scenarios are discussed, and commercially available cytokine assays are compared. A discussion of challenges in the development and advancement of technologies for cytokine quantification that aim to achieve real‐time multiplex cytokine analysis for point‐of‐care situations applicable for both biomedical research and clinical practice are discussed. Abstract : Cytokines are important cellular signaling molecules and immune system mediators. Abnormal cytokine levels may cause cytokine storm and diseases. Consequently, quantification of cytokines is valuable for diseases diagnosisand therapy. The clinical significance of cytokines, factors affecting cytokine quantification, and advances of cytokine detection are summarized, providing a prospective for real‐time quantification of multiplex cytokines in the clinic.